Peran Filsafat Ilmu terhadap Ilmu Ekonomi dan Pengembangan Para Sarjananya - Nasrullah, Yazid (Unisia, 2012)
Philosophy of Science significantly contributes to the development of Economics toward the improvement of economical science and analyses as well as the improvement of quality of Economists, having capability of thought, of behaving and of acting as wise scholars. The roles of Philosophy of science in developing Economics have been: as a tool of evaluation of scientific thinking; as an instrument to reflect, evaluate, criticize assumptions and scientific methods; and as a tool of basic logic for scientific methods. Keywords: Economics, economics scholars. Philosophy of science.